Ответы и объяснения

2013-01-24T15:21:59+00:00

12+3(х-1)=0

12+3х-3=0

3х=-12+3

3х=-9

х=-3

1-5(2-3х)=6

1-10+15х=6

15х=6+10-1

15х=15

х=1

2013-01-24T15:27:21+00:00

x-1=12+3*0                                                                                                                                                          х-1=12                                                                                                                                                                 х=12+1                                                                                                                                                                х=13